My Glorious Opportunity: How My Dementia Has Been a Gift. Issue 1 (2nd April 2016) - Bute, Jennifer
Abstract : This article is a personal reflection on the experience of living with dementia. Jennifer Bute is a former family practitioner who has early-onset Alzheimer's disease. The article presents some basic principles for living well with dementia and offers some deep and personal reflections on what it means, how it can be understood theologically, and how all of us together can help one another to live well with dementia.